Exploring barriers to oral health among young carers in Surrey, England. (November 2017) - Kaddour, Sarah; Sowerbutts, Jackie; Shah, Samit
Abstract: Background: Young carers are individuals under 18 years old who care for someone with a condition or disability. This vulnerable group in society provides valuable care that sometimes compromises their own wellbeing, including their oral health. Very little research has been conducted into the barriers to oral care faced by this group. Local authorities are now responsible for oral health improvement. Because there are a large number of young carers in Surrey, a county in the south of England, the local authority wanted to investigate how these young people felt about their own oral health and dental service experience. This study is an example of how local authorities are promoting oral health in an underused population to explore themes around oral health and access to services. We aimed to explore the barriers that young carers experience in accessing dental services and maintaining their oral health. Methods: A dental public health core trainee from Health Education England attended two young carers forums that were part of an informal activities evening. 24 young carers attended across the two sessions. Pictures were used on an iPad and circulated around the groups to help aid discussion. The pictures described dental disease, oral hygiene aids, and foods and drinks that could be detrimental to oral health. Topics explored were self-care, oral care for a relative, accessing a dentist, emergency care, dental anxiety, orthodontics, and tooth whitening. Findings: The themes gathered were: difficulty in accessing care, both for the carer and the relative they cared for; accessing emergency care; anxiety when looking after a relative's teeth; dental anxiety; and awareness of hidden sugars. Interpretation: Our findings show that young carers are unable to access dental services for themselves and for the relatives they care for. They have the additional pressures of looking after the oral health of a relative as well as their own. More awareness and support is needed for this unique and valuable group. Further exploration around these themes could be beneficial to see how best to meet the oral health requirements of young carers. Funding: None.